2021
DOI: 10.1177/0300060520985338
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of cervical length by ultrasound and cervical strain elastography in labor induction at term

Abstract: Objective This study aimed to examine whether addition of cervical elastographic parameters measured by ElastoScan for the cervix (E-cervix) improves the predictive value of cervical length (CL) in induction of labor at term by dinoprostone. Methods We conducted a prospective, observational study between January 2020 and June 2020 in term primiparous women (n = 73) who were scheduled for labor induction by a 10-mg dinoprostone vaginal insert. The time intervals from the start of labor induction to regular uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…The functional cervical length can be measured using the E-Cervix system and a four-point ROI that traces the endocervical lining of a straight or curved cervix [ 27 ]. The accuracy and repeatability of cervical length measurements have been improved using semi-automatic systems, and cervical length has become a valuable parameter for predicting the success of IOL [ 13 , 28 31 ]. Hamza et al reported that a cervical length of 25 mm, the presence of cervical funneling, and a shorter cervical length were significantly associated with successful IOL within 24 h [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional cervical length can be measured using the E-Cervix system and a four-point ROI that traces the endocervical lining of a straight or curved cervix [ 27 ]. The accuracy and repeatability of cervical length measurements have been improved using semi-automatic systems, and cervical length has become a valuable parameter for predicting the success of IOL [ 13 , 28 31 ]. Hamza et al reported that a cervical length of 25 mm, the presence of cervical funneling, and a shorter cervical length were significantly associated with successful IOL within 24 h [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eser et al reported that cervical length is significantly related to a satisfactory response to IOL and the time from induction to delivery [ 30 ]. Zhou et al found that a short cervical length and a soft cervix are significantly associated with vaginal delivery within 24 h, and that the use of cervical strain elastography could improve the predictive performance of cervical length for a successful vaginal delivery within 24 h of IOL [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have analyzed the connection between elastographic findings and induction of labor by prostaglandins [21]. Carlson et al revealed that cervical softening after misoprostol was clearly associated by the measurements in elastosonography, although, they did not provide a correlation with induction success [22].…”
Section: Discussionmentioning
confidence: 99%
“…In one of the reports published in 2019, the inclusion of the ECI parameter in the logistic regression model containing three other parameters (CL, prepregnancy BMI and gestational age at examination) for patients in the second trimester of pregnancy with cervix length ≥ 1.5 cm significantly increased the overall diagnostic accuracy of the test compared to screening based solely on CL 4 . In the perinatal period, some of the E-Cervix parameters (HR, IOS) in combination with CL allowed for increasing the predictive capacity of the model evaluating the chance of vaginal delivery in the next 24 h during labour induction with the use of a dinporoston vaginal insert 6 . Perhaps further research in elastography will contribute to its wider use in obstetrics.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical hardness is a standard element assessed in the bimanual examination of the pelvis during pregnancy, and it is also an element of the Bishop scale assessment 2 . Consistency examination can be used in the prediction of preterm labour 3 , 4 , in the prediction of a spontaneous onset of labour and in evaluations of the effectiveness of the induction of labour (IOL) 5 , 6 . The two main techniques of USE are strain elastography (SE) and shear wave elastography (SWE), differing in terms of the stress type applied to tissue.…”
Section: Introductionmentioning
confidence: 99%